Sovereign wealth fund investment patterns and performance - Bernardo Bortolotti; Veljko Fotak; William L. Megginson; William Miracky (Fondazione Eni Enrico Mattei (FEEM), 2009)
We examine 802 investments by 33 Sovereign Wealth Funds (SWFs) in publicly traded companies between May 1985 and November 2009, and find that SWFs tend to invest in large, levered, profitable growth firms, usually headquartered in an OECD country. Announcements of SWF investments yield significantly positive abnormal stock price returns, averaging 1.25% (2.91% excluding the 403 purchases of U.S.-listed stocks by Norway's fund) over a three-day (-1,+1) event window, but most investments lead to deteriorating firm performance over the following two years, with significantly negative mean abnormal returns of up to -6.25% (median of up to -14.71%) over 2-year holding periods. Our results are robust to the use of different benchmarks and event study methodologies. We examine whether sovereign funds acquire representation on the boards of directors of 355 target firms in the years after initial investment; funds acquire seats in only 53 companies, or in only 14.9% of all cases, though this percentage rises to 26.8% when the 157 targets of Norway's fund are excluded. Poor long-term stock performance is linked to the degree of involvement of the SWF: abnormal performance worsens the larger the stake acquired, if the investment is direct, rather than through subsidiaries or investment vehicles, and if the SWF takes a seat on the board of directors. Underperformance is also worse for investments in foreign firms. Analysis of post-investment performance using accounting variables validates the event-study findings of poor long-term performance. These findings support our Constrained Foreign Investor Hypothesis, which predicts that foreign investors, especially large, state-owned ones such as SWFs, will be unable to exercise proper monitoring due to pressures not to antagonize local management.
Keywords: G32; G15; G38; 330; Sovereign Wealth Funds; International Financial Markets; Government Policy and Regulation